2019
DOI: 10.1111/tog.12619
|View full text |Cite
|
Sign up to set email alerts
|

‘Perfect practice makes perfect’: the role of laparoscopic simulation training in modern gynaecological training

Abstract: Unique psychomotor and perceptual challenges of laparoscopysuch as marred depth perception, the requirement for advanced hand-eye coordination and the use of long instrumentsmean that laparoscopic trainees face a steep learning curve. The difficulties that trainees encounter in meeting required laparoscopic competencies may, in part, be overcome through the use of laparoscopic simulation training (LST), with benefits for trainees, patients, consultant staff and hospital budgets. There is growing evidence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…There are ethical concerns raised over surgeons learning on real patients given that more experienced surgeons often attain better outcomes 28 , so increasing surgical experience through simulation-based training is a safer method for reducing the learning curve associated with procedures 132 . Mentorship is another educational intervention that has been demonstrated to reduce the surgical learning curve 133 , with the ‘Leipzig Model’ of supervision in LRP being one such example 134 .…”
Section: Discussionmentioning
confidence: 99%
“…There are ethical concerns raised over surgeons learning on real patients given that more experienced surgeons often attain better outcomes 28 , so increasing surgical experience through simulation-based training is a safer method for reducing the learning curve associated with procedures 132 . Mentorship is another educational intervention that has been demonstrated to reduce the surgical learning curve 133 , with the ‘Leipzig Model’ of supervision in LRP being one such example 134 .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical skills learnt on simulators can be transferred to real patient surgery, but these benefits are mostly observed with repetitive practice and as part of a structured simulation programme 34–36. The latter is promoted as a solution for bridging the gap between required operative skills and reduced training opportunities 37 38. In this context, the American College of Obstetricians & Gynecologists has included a structured simulation programme, as part of board certification for practice in O&G 39…”
Section: Discussionmentioning
confidence: 99%
“…7 Simulation leads to skill acquisition 8 and improves student confidence; 9 it is therefore considered to be valuable as an educational strategy, specifically within the field of EMC. Although it has been reported that simulation as an educational strategy improves confidence, it has also been found to cause anxiety, 8,10 especially when used for assessment purposes. 11 There is extensive use of simulation for assessment in South African EMC programmes, where students are required to treat medium-to high-fidelity simulated patients in a clinical scenario.…”
Section: Introductionmentioning
confidence: 99%